Evaluating Student Perceptions of Open and Commercial Psychology Textbooks - Howard, Veronica J.; Whitmore, Corrie B. (Frontiers in Education, 2020)
Abstract Prior studies on students’ perception of open educational resources (OERs) indicates that students find open resources as good or better than commercial textbooks (Hilton, 2016). However, studies published to date have not attempted to control for student knowledge of cost as a variable influencing perception of quality. The purpose of this study was to evaluate students’ perception of the quality of brief, de-identified open and commercial textbook samples, then determine whether their preferences changed after learning textbook costs. As part of an in-class activity, students enrolled in an introductory-level psychology course reviewed samples of two commercial and two open textbooks. Participants rated the materials on quality measures (Gurung & Martin, 2011), selected a preferred textbook, and provided a rationale for their choice. Next, participants were informed of the cost of each textbook and asked to re-rate textbook quality and indicate whether their textbook preference had changed. Prior to learning the cost of the textbooks from which each sample was selected, 81.29% of responding participants indicated preference for a specific commercial text, citing quality factors related to quality/clarity of writing, book layout, and quality of figures as primary drivers of preference. Following the cost reveal, only 42.46% of responding participants indicated a preference for a commercial textbook while 57.53% indicated a preference for an open textbook. An exact McNemar’s test determined that this was a statistically significant difference in the proportion of respondents who selected open and commercial texts before and after price data were available, p < .01. Qualitative comments for participants who indicated a preference shift toward the open textbook referenced cost and quality of the materials as components of their decision-making, supporting previous studies that demonstrate cost is an important predictor of students’ textbook preferences (Clinton, 2019). Regression analysis showed that visual appeal, engaging writing, and clarity of writing predicted participants’ desire to use the text in class, but quality of examples was only a significant predictor for one of four texts. Suggestions for future research are discussed.